The red devils - Waring, Rob; Roehrseries, Sherrise; Heinle Cengage Learning ([London] : Heinle Cengage Learning, 2010)
Humboldt squids or'Red Devils' are some of the world's largest animals without a backbone. These sometimes dangerous creatures live in the deep waters of the Oacific Ocean
Book title is'The red devils'
Title from container
Footprint Reading Library with video from National Geographic
Video and Audio on DVD
Keywords: Squids